Model Analysis of Environmental and Economic Impacts of a Microgrid Based on the Optimization Method - Pengxiao Ji (Advances in Multimedia)
In order to improve the synergistic effect of a microgrid and its economic impact, this paper applies the optimization method to the improvement of microgrid operation. On the basis of studying the bilevel optimization theory, this paper applies the bilevel optimization theory to the economic dispatch of the microgrid and constructs a bilevel economic dispatch model of the microgrid considering the environmental benefits. Moreover, considering the environmental benefits of the microgrid two-level economic dispatch model, this paper constructs an intelligent analysis model and uses the deep learning algorithm as the system learning algorithm to improve the system data processing capability. The simulation study verifies that the optimal solution model of the microgrid environment and economic impact based on the optimization method has a good effect, and the method in this paper can effectively improve the microgrid operating environment and economic benefits.